2021
DOI: 10.1186/s12879-021-05873-7
|View full text |Cite
|
Sign up to set email alerts
|

Maximal diameter of liver abscess independently predicts prolonged hospitalization and poor prognosis in patients with pyogenic liver abscess

Abstract: Background/aims This study aimed to investigate the factors associated with prolonged hospital stay and in-hospital mortality in patients with pyogenic liver abscess. Methods We retrospectively reviewed data from patients with pyogenic liver abscess who were admitted between 2005 and 2018 at three tertiary hospitals in Jeonbuk province, South Korea. Prolonged hospital stay was defined as a duration of hospital admission of more than 21 days. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 35 publications
3
35
0
1
Order By: Relevance
“…Though E. coli was less common than K. pneumoniae in PLA, it showed higher rate of antibiotic resistance with 42.9% producing ESBL. These findings were similar to previous studies in Asian countries [ 25 , 26 ]. The bacterial spectrum may be useful in empiric antibiotic decision making.…”
Section: Discussionsupporting
confidence: 93%
“…Though E. coli was less common than K. pneumoniae in PLA, it showed higher rate of antibiotic resistance with 42.9% producing ESBL. These findings were similar to previous studies in Asian countries [ 25 , 26 ]. The bacterial spectrum may be useful in empiric antibiotic decision making.…”
Section: Discussionsupporting
confidence: 93%
“…[1,12,17] In their randomised trial, Lee et al showed that particular predictors for protracted hospital admissions were: diabetes mellitus; arterial hypertension; positive identification of bacteria in culture; and reduced Hb values at the time of diagnosis Independent risk factors identified as part of the trial also included an abscess diameter of >5 cm, and a significantly elevated CRP. [15] If these factors were to be considered for the case we have presented here, then the initially poor prognosis for our case would have been associated with an indication for an in-patient hospital stay >14 days as well as surgical treatment of the liver abscess with percutaneous drainage. [9,18] There are no data that recommend or consider purely conservative therapy possible for large or multifocal liver abscesses.…”
Section: Discussionmentioning
confidence: 97%
“…Mortality increases with increasing size of the abscess, and with decreasing Hb values. [14,15] Case A 50-year-old male patient was referred to our clinic with the diagnosis of "liver tumour of unclear type". On examination the patient was obese (115kg; 187cm; BMI: 32.9), and had presented to the doctor due to a deterioration in his condition.…”
Section: Introductionmentioning
confidence: 99%
“…In their randomized trial, Lee et al showed that particular predictors for protracted hospital admissions were as follows: diabetes mellitus; arterial hypertension; positive identification of bacteria in culture; and reduced Hb values at the time of diagnosis. Independent risk factors identified as part of the trial also included an abscess diameter of >5 cm and a significantly elevated CRP 15 . If these factors were to be considered for the case we have presented here, then the initially poor prognosis for our case would have been associated with an indication for an in‐patient hospital stay >14 days as well as surgical treatment for the liver abscess with percutaneous drainage 9,18 …”
Section: Discussionmentioning
confidence: 99%
“…Liver abscesses with a diameter of up to 5 cm can be treated conservatively using antibiotics alone with a very good prognosis; larger abscesses, by contrast, should be additionally treated using percutaneous drainage or surgery. Mortality increases with increasing size of the abscess and with decreasing Hb values 14,15 …”
Section: Introductionmentioning
confidence: 99%